Family cohesion and quality of life significantly affecting personality changes in adult epilepsy patients: a case-control study - Jiaai Li; Salamaitiguli Mijiti; Yinyin Xie; Jingqi Lin; Lixia Zhu; Hongmei Meng (BMC, 2024)
Abstract Objective The goal of epilepsy treatment is not only to control convulsive seizures but also to improve the quality of life of patients. This study aimed to investigate personality changes and the risk factors for their development in adult epilepsy patients. Methods A case-control study in a Class III, Class A hospital. The study comprised 206 adult epilepsy patients admitted to the Neurology Department at the First Hospital of Jilin University between October 2019 and December 2021, while the control group consisted of 154 community volunteers matched with the epilepsy group based on age, sex, and education. No additional treatment interventions were determined to be relevant in the context of this study. Results There is a significantly higher incidence of personality changes in epilepsy than in the general population, and patients with epilepsy were more likely to become psychoticism, neuroticism, and lie. Epilepsy patient's employment rate and average quality of life score were significantly lower than that of the general population and had strong family intimacy but poor adaptability in this study. There are many factors affecting personality change: sleep disorders, economic status, quality of life, use of anti-seizure drugs, family cohesion and adaptability. The independent risk factors were quality of life and family cohesion.